Polymeric Composite-Based Electrochemical Sensing Devices Applied in the Analysis of Monoamine Neurotransmitters - Stelian Lupu (Biosensors, 2025)
Electroanalysis of monoamine neurotransmitters is a useful tool for monitoring relevant neurodegenerative disorders and diseases. Electroanalysis of neurotransmitters using analytical devices consisting of electrodes modified with tailored and nanostructured composite materials is an active research topic nowadays. Nano- and microstructured composite materials composed of various organic conductive polymers, metal/metal oxide nanoparticles, and carbonaceous materials enable an increase in the performance of electroanalytical sensing devices. Synergistic properties resulting from the combination of various pristine nanomaterials have enabled faster kinetics and increased overall performance. Herein, recent results related to the design and elaboration of electroanalytical sensing devices based on cost-effective and reliable nano- and microstructured composite materials for the quantification of monoamine neurotransmitters are presented. The discussion focuses on the fabrication procedures and detection strategies, highlighting the capabilities of the analytical platforms used in the determination of relevant analytes. The review aims to present the main benefits of using composite nanostructured materials in the electroanalysis of monoamine neurotransmitters.